Development of Barefoot trace recognition system - DOUNIA, taabli; Kawther, Hadjaidji (My University, 2022)
In the past, tracking science was known as ’Al-Qiyafah’ science, in which an expert nomad deduce vital information about a person from its footprints. In addition, one of the most popular fields in computer vision is human identification. Biometric identification using the finger or iris, or a footprint scan, is the most promising method currently being researched for this purpose. Because foot traces lack biometric characteristics, the process of recognizing people using them is far more difficult than using footprints. The goal of this project is to turn ’Al-Qeiyafah’ procedure into an intelligent system. Using image processing techniques, the system extracts foot trace features from an input image. Advanced deep learning approaches are used in the tracing identification system to help discover traces and recognize the attributes of each trace quickly. We employ the convolution neural networks approach in the suggested system to estimate the foot trace owner based on attributes derived from the performed system. For this objective, we proposed our system, Where We will train a convolutional neural network that predicts age and gender from an image containing a person’s footprint by using a CNN model for extracting the image’s features. the model is composed of two parts, a pre-trained model and a classifier. The pre-trained VGG16 model was nominated for integration into the system classifier (Softmax). The obtained results show clearly their accuracy, As the program was working efficiently, we eventually obtained satisfactory results, where the accuracy was 96.5%, but it is still insufficient to solve the aspect of human Barefoot traces recognition. In addition, somë Dans le passé, la science du suivi était connue sous le nom de qayyafa, dans laquelle un expert bédouin déduit des informations vitales sur une personne à partir de ses empreintes. De plus, la reconnaissance humaine est l’un des domaines les plus populaires de la vision par ordinateur. L’identification biométrique utilisant le bout du doigt ou l’iris, ou l’empreinte digitale, est la méthode la plus prometteuse actuellement étudiée à cette fin. Parce que les empreintes des pieds n’ont pas de propriétés biométriques, il est beaucoup plus difficile d’identifier les personnes qui les utilisent que d’utiliser des empreintes de pieds. L’objectif de ce projet est de transformer la procédure de « qayyafa » en un système intelligent. À l’aide des techniques de traitement d’image, le système extrait les caractéristiques de suivi du pied à partir de l’image d’entrée. Des approches avancées d’apprentissage en profondeur sont utilisées pour aider à détecter les traces et identifier rapidement les attributs de chaque trace. Nous utilisons une approche de réseau neuronal convolutionnel dans le système proposé pour estimer le propriétaire du pied en fonction des attributs dérivés du système mis en œuvre. Pour cet objectif, nous avons proposé un système, où nous formerons un réseau neuronal convolutif qui prédit l’âge et le sexe à partir d’une image contenant l’empreinte digitale d’une personne en utilisant un modèle CNN pour extraire les caractéristiques de l’image. Le modèle se compose de deux parties, un modèle pré-formé et classifié. Le modèle VGG16 pré-entraîné a été choisit pour être intégré dans un système de classification (Softmax). Les résultats obtenus montrent clairement une bonne précision de 96.5%, mais reste insuffisant pour résoudre l’aspect de la reconnaissance de traces pieds nus. De plus, certains aspects pourraient être améliorés.
mémoire master informatique
Keywords: traitement d’images, réseau de neurones convolutifs, couche Softmax, VGG16, modèle pré-entraîné, foot tracking, barefoot tracking, classification de modèles binaires, classification multi-modèles.; Image processing, Convolutional Neural Network, Softmax layer, VGG16, Pre-trained model, Foot trace, Barefoot trace, binary Model classification, Multi-Model classification. iv